'Not everyone can be a Gandhi': South Asian-trained doctors immigrating to Canada, c. 1961–1971. Issue 4 (3rd July 2016) - Wright, David; Mullally, Sasha
Abstract : Objectives . This paper will explore the social history of the transnational migration of foreign-trained doctors to western countries in the post-WWII era, by examining, as a case study, South Asian-trained doctors who were first licensed in the Canadian province of Nova Scotia between 1961 and 1971.Design . This article draws on both quantitative and qualitative primary sources. First, we analyzed the 1966 and 1971 copies of the Canadian Medical Directories (CMD), the annual compendium of all licensed practitioners in the country (over 20, 000 practitioners). These CMD entries were supplemented by the annual returns of 'intended occupation' (those designated as 'physician' or 'surgeon') of landed immigrants to Canada, as compiled by the federal Department of Manpower and Immigration. Secondly, we analyzed testimony of 26 oral histories and narrative accounts of foreign-trained doctors being compiled as part of an ongoing multiyear program of research on the immigration of foreign-trained doctors to Canada. We have interviewed 14 doctors who, at one point in their career, practiced in Nova Scotia, 8 of whom were South Asian-trained medical practitioners. These oral interviews provide personal reflections on the process of professional and social acculturation that occurred as these foreign doctors settled in Canada.Results. The results of this paper indicate that the social history of the immigration of South Asian-trained doctors to Canada in the 1960s must be seen within a larger and more complicated pattern of the international migration of health care professionals. Indeed, the demand for foreign-trained doctors in Britain was in part a reflection of the out-migration of British-born doctors who were leaving the National Health Service for Canada, the USA, and Australia. And the demand in Canada for doctors was itself a reaction to the drift of a certain number of Canadian-trained doctors for advanced training in the USA.Conclusions . In this way, this article sheds important historical perspectives on the globalization of health human resources and the complicated, multiple migrations that continue to animate international health human resources today.